PENGENALAN APLIKASI DATA STATISTIK FUTSAL TIM 5 (FIVE) PADA PELATIH-PELATIH FUTSAL DI WILAYAH JAKARTA TIMUR - Andri Irawan Irawan; Nur Fitranro (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Partners in this community service program are trainers in the east Jakarta area.The purpose of this activity is to provide an introduction to the application of futsal-specific statistical data called TIM 5 (FIVE) which has been developed by student research results at the Faculty of Sports Sciences, Universitas Negeri Jakarta. This application provides information about basic techniques, and tactics in futsal games with accurate data so that it can be analyzed for the progress of the team.The implementation of community service is carried out online via zoom meeting with the number of east Jakarta futsal coach participants as many as 20 coaches.The result of this community service is from 20 coaches 9 people or 45% of participants expressed very interested and 5 people or 10% of participants interested in using the application.It is expected that with the introduction of this application the coaches become interested or interested in using the services or getting this application software for the development of futsal teams so that the coached team is growing. Abstrak Mitra dalam program pengabdian masyarakat ini adalah para pelatih di wilayah Jakarta timur. Tujuan dari kegiatan ini adalah untuk memberikan pengenalan mengenai aplikasi data statistic khusus futsal yang bernama TIM 5 (FIVE) yang telah di kembangkan hasil penelitian mahasiswa di Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta. Aplikasi ini memberikan informasi mengenai teknik dasar, dan taktik dalam permainan futsal sengan data-data yang akurat sehingga bisa di analisis untuk kemajuan tim. Metode Pelaksanaan pengabdian msyarakat ini dilakukan secara daring via zoom meeting dengan jumlah peserta pelatih futsal Jakarta timur sebanyak 20 orang pelatih. Hasil pengabdian msyarakat ini adalah dari 20 orang pelatih 9 orang atau 45% peserta menyatakan sangat berminat dan 5 orang atau 10% peserta berminat menggunakan aplikasi. Diharapkan dengan adanya pengenalan aplikasi ini para pelatih menjaditertarik atau berminat untuk menggunakan jasa atau mendapatkan software aplikasi ini untuk pengembangan tim futsal agar tim yang di latih semakin berkembang.